Inscripciones de escrituras de compraventa tardías y el principio de celeridad - Iza Ango, Erika Tamara (2025)
This article will review and study how the process of registration of late deeds of sale is carried out and how it is influenced by the principle of celerity. As society progresses, it is forced to make progress in several areas, one of them being in the field of law, progressing in laws, norms, ordinances and resolutions. The main objective of this research is to analyze how the property registry should act and proceed to register a late deed of sale, and if it can be evidenced that there is any vice or not fully comply with the established rules, safeguarding the rights of buyers, as well as the rest that could be affected by this late registration. The proposed methodology was qualitative, focusing on the study, interpretation and use of this information to verify how property registrars handle this type of cases, their requirements and the time taken to conclude the registration procedure. Finally, it will conclude with a review of the process, which is carried out in an effective and efficient manner, complying with the principle of celerity.